2011
DOI: 10.1002/cpp.712
|View full text |Cite
|
Sign up to set email alerts
|

Occupational functioning, sickness absence and medication utilization before and after cognitive–behaviour therapy for generalized anxiety disorders

Abstract: The data suggest that CBT is not only efficacious in terms of symptom reduction but also efficient in terms of reducing inappropriate medication intake and improving occupational functioning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 42 publications
(45 reference statements)
0
13
0
2
Order By: Relevance
“…Treatment studies examining the efficacy of CBT for adult anxiety suggest that treatment responders evidence improvement in occupational functioning, in addition to anxiety symptom reduction. Similarly, in a study examining CBT treatment outcomes for adults with GAD, participants showed a significant decrease in impairment related to work performance, adjustment to work routines, and interpersonal relationships with colleagues from pre-to posttreatment and at follow-up (Linden, Zubr€ agel, & B€ ar, 2011). After receiving treatment, adults who demonstrated symptom improvement also demonstrated improvement in overall work performance and interpersonal functioning while at work, but not work attendance.…”
Section: Treatmentmentioning
confidence: 90%
See 1 more Smart Citation
“…Treatment studies examining the efficacy of CBT for adult anxiety suggest that treatment responders evidence improvement in occupational functioning, in addition to anxiety symptom reduction. Similarly, in a study examining CBT treatment outcomes for adults with GAD, participants showed a significant decrease in impairment related to work performance, adjustment to work routines, and interpersonal relationships with colleagues from pre-to posttreatment and at follow-up (Linden, Zubr€ agel, & B€ ar, 2011). After receiving treatment, adults who demonstrated symptom improvement also demonstrated improvement in overall work performance and interpersonal functioning while at work, but not work attendance.…”
Section: Treatmentmentioning
confidence: 90%
“…• Youth anxiety in combination with depression may confer risk for unemployment and lower household income (Last et al, 1997) • Adult anxiety treatment studies indicate that efficacious treatment is associated with improved occupational functioning, in addition to symptom reduction (Erickson et al, 2009;Linden et al, 2011). • No studies have examined the impact of anxiety treatment in youth on occupational functioning in adulthood.…”
Section: Academic Functioningmentioning
confidence: 99%
“…In a review, Mintz et al found that psychotherapy significantly improved occupational functioning assessed with the Social Adjustment Scale (SAS) for patients with depression [13], but another review did not find that intervention had a significant effect on occupational functioning [14]. We identified nine studies on intervention for non-psychotic mental disorders measuring sick leave absence and found that they all reported that psychotherapy led to a reduced number of sick leave days [9,[15][16][17][18][19][20][21][22]. The most recent study, conducted by Linden et al, investigated 44 patients treated with cognitive behavioral therapy for anxiety disorders.…”
Section: Introductionmentioning
confidence: 99%
“…The most recent study, conducted by Linden et al, investigated 44 patients treated with cognitive behavioral therapy for anxiety disorders. During the eight months prior to intake, the patients had an average of 3.1 sick leave days per month (the equivalent of 37.2 days per year), whereas the average was only 1.1 days per month in the eight months after treatment (equals 13.2 days per year) [22].…”
Section: Introductionmentioning
confidence: 99%
“…In depressed individuals, antidepressant medication has been shown to increase work productivity 6 and psychodynamic therapy (with or without adjunctive antidepressant medication) has been shown to reduce self‐reported absenteeism 7 , 8 . In individuals with anxiety disorders, face‐to‐face CBT has been shown to increase work productivity 9 . For a range of anxiety and affective disorders, face‐to‐face CBT combined with occupational therapy has been shown to improve occupational functioning 10 .…”
mentioning
confidence: 99%